PERAN ACT INDONESIA DALAM MENANGANI KORBAN KONFLIK DI GAZA, PALESTINE - Annisa Alya Shabita; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aim to describes the role of ACT (Aksi Cepat Tanggap) Indonesia as an non-profit organization engaged in humanity to helps the victim of disaster and the victims of war in conflict-affected area. Since the conflict began, Palestinian faced the situation that took their rights. Shooting, detention and bombing, affect the humanitarian crisis in Palestine. The amount of damage to infrastructure and the difficulty of getting food and medicine, makes Palestinian suffering more difficult. The research use pluralism perspective which believes that states are not the only actors in International world. This research is also guided by theory of role. The method used is qualitative method. The data collection incorporates interviews and literature study from some journals, books, documents and websites. This research shows the action by ACT Indonesia in dealing with the victims by excecuting programs that has been created for the victims and this research also explained the obstacles that ACT Indonesia faced to help victims of war in Palestine and the result of helping and advocacy they have made. This research concludes that ACT Indonesia had a program in dealing with victims of conflict in Palestine, the assistance provided ACT Indonesia was able to help the survival of the Palestinian. Keywords : Role, ACT Indonesia, Conflict, Humanity Crisis, Gaza, Palestina, NGO, Transnational, Advocacy